THE EFFECT OF DIFFERENT ADSORBING AGENT AS PURIFIER ON SMOKED-COPRA OIL CHARACTERISTIC - Giffary Pramafisi Soeherman; Fahrulsyah Fahrulsyah; Iyan Indrawan (Politeknik Negeri Lampung, 2023)
Efforts that can be made in clarifying copra oil made by the smoking method are absorption by adsorbents such as activated charcoal, zeolite, and bleaching earth. The adsorbent can be used for decolourizing and deodorizing. This research aims to determine the characteristics of purified smoked copra oil using different absorbents. Copra oil is weighed properly and the weight is recorded. Each absorbent material as much as 5% (w/w) of oil is added to the oil which has been heated at 70°C. Purification was carried out for 2 hours at a temperature of 70-75°C. The purification process is carried out in one stage. The oil is then filtered using filter paper (separating absorbent material and pure oil). The oil obtained was then subjected to free fatty acid (ALB) and organoleptic analysis. Based on the research results, purification with zeolite adsorbent resulted in the largest ALB reduction with a decrease value of 39.71%. Judging from the organoleptic characteristics, zeolite can significantly reduce the intensity of the brown color, the intensity of the coconut aroma, and the intensity of the rancid aroma. Activated charcoal can significantly reduce the intensity of the brown color, the aroma of smoke, the distinctive aroma of coconut and the rancid aroma of copra oil, while bleaching earth provides a marked reduction in the intensity of the brown color of the oil which at the same time provides a significant increase in oil clarity. The use of absorbent materials can affect the characteristics of smoked copra oil so that it has the potential to improve the quality of smoked copra oil.